Losing the carbon game? Changing face of a tropical smart metro city and its repercussions on carbon sequestration, heat and flood mitigation capacity - Pratiksha Chalke; Pankaj Koparde (Sustainable Futures)
Tropical areas are rich in biodiversity but adversely getting affected by non-sustainable rapid development and climate change. Pune city is a tropical smart metro city of India, located on the edges of the Western Ghats biodiversity hotspot. The city is surrounded by hills and is lined by four rivers. The city is a cultural, heritage, educational, and IT hub and is expanding rapidly. In the context of rampant urbanization and intensification in tropical metro cities, the present study utilizes GIS and RS tools to investigate the dynamic transformation of Pune city’s landscape from 2013 to 2022. Here we analyze four indices for Pune city, namely, carbon sequestration capacity, flood and heat mitigation capacity, and vegetation dynamics over a decade. The paper explores consequential shifts in land use and land cover, employing advanced modeling techniques, specifically the InVEST software. We report a rapid rise in built-up area by 12 % at the loss of scrubland (16 %) when compared data from 2013 to 2022. The years 2020–2022 showed a spike in NDVI values and lowering of Land Surface Temperature, correlated with less human activity owing to the city-wide lockdown during COVID-19 pandemic. Our analysis revealed that the city has lost its carbon sequestration capacity by 34 % and flood mitigation capacity by 13 % when compared data from 2013 to 2022. Hills of Pune exhibit a higher heat mitigation compared to the rest of the area. Our results highlight the importance of native geological features such as hills in carbon sequestration, heat and flood mitigation. Our research implies that sustainable development in tropical metro cities can be achieved by leveraging native features rather than undermining them.